Social learning, influence, and ethnomedicine: Individual, neighborhood and social network influences on attachment to an ethnomedical cultural model in rural Senegal. (April 2019) - Sandberg, John; Park, Chulwoo; Rytina, Steven; Delaunay, Valerie; Douillot, Laetitia; Boujija, Yacine; Gning, Sadio Ba; Bignami, Simona; Sokhna, Cheikh; Belaid, Loubna; Diouf, Insa; Fotouhi, Babak; et al.
Abstract: The preference in many parts of the world for ethnomedical therapy over biomedical alternatives has long confounded scholars of medicine and public health. In the anthropological literature cultural and interactional contexts have been identified as fundamental mechanisms shaping adherence to ethnomedical beliefs and health seeking behaviors. In this paper, we examine the association between individual, neighborhood, and social network characteristics and the likelihood of attachment to an ethnomedical cultural model encompassing beliefs about etiology of disease, appropriate therapeutic and preventative measures, and more general beliefs about metaphysics and the efficacy of health systems in a rural population in Eastern Senegal. Using data from a unique social network survey, and supplemented by extensive qualitative research, we model attachment to the ethnomedical model at each of these levels as a function of demographic, economic and ideational characteristics, as well as perceived effectiveness of both biomedical and ethnomedical therapy. Individuals' attachment to the ethnomedical cultural model is found to be strongly associated with characteristics of their neighborhoods, and network alters. Experiences with ethnomedical care among neighbors, and both ethnomedical and biomedical care among network alters, are independently associated with attachment to the ethnomedical model, suggesting an important mechanism for cultural change. At the same time, we identify an independent association between network alters' cultural models and those of respondents, indicative of a direct cultural learning or influence mechanism, modified by the degree of global transitivity, or 'connectedness' of individuals' networks. This evidence supports the long held theoretical position that symbolic systems concerning illness and disease are shared, reproduced, and changed through mechanisms associated with social interaction. This has potentially important implications not only for public health programming, but for the understanding of the reproduction and evolution of cultural systems more generally. Highlights: Models attachment to ethnomedical belief system (cultural model) in rural Senegal. Investigates role of individual, neighborhood, and social network characteristics. Experience of biomedical and ethnomedical care among network alters key. Direct social learning of cultural model between respondent and network alters. Social learning modified by network transitivity, or 'connectedness'.